PENGARUH PEMAHAMAN PAJAK DAN PENERAPAN PP NOMOR 23 TAHUN 2018 TERHADAP TINGKAT PENERIMAAN PAJAK UMKM DI KPP PRATAMA PURWOREJO - , (Politeknik Sawunggalih Aji, 2023)
UMKM are businesses owned by individuals or entities that have met the criteria for micro-businesses. UMKM have an important role in the Indonesian economy. The UMKM sector is able to absorb large-scale workforce that is able to reduce the unemployment rate in Indonesia. In the last few years in Purworejo district, UMKM business actors have increased every year, but the increase has not been in line with the taxation sector, where the contribution of UMKM to the taxation sector has not had a maximum effect. There are still many UMKM who avoid tax even though the government has implemented an easy taxation policy. The taxation sector is one source of state revenue. The Government of Indonesia issued a new policy related to reducing tax rates for UMKM actors by 0.5% intended to facilitate UMKM actors in fulfilling their tax obligations and to increase tax revenue from the UMKM sector so that the increase in the number of UMKM actors can be in line with the increase in UMKM sector tax revenues. This study aims to determine the effect of understanding tax and the application of PP No. 23 of 2018 on the level of UMKM tax acceptance. In this study the population and sample used are UMKM taxpayers in Purworejo district and registered with the KPP Pratama Purworejo with a sample size of 100. The data used are primary data, research instruments used in the form of questionnaires, and data processing using SPSS version 20.0. The results of this study based on the analysis conducted, it can be concluded that the understanding of tax and the application of PP No. 23 of 2018 has a positive and significant effect on the level of UMKM tax revenue with an R-Square value of 0.490. Understanding tax partially affects the level of UMKM tax revenue with a significant value of 0,000 and the application of PP No. 23 of 2018 does not affect the level of UMKM tax revenue. Understanding tax and the application of PP Number 23 Year 2018 simultaneously affect the level of tax revenue with a significance value of 0,000.